2018
DOI: 10.1159/000487644
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life after Radical Cystectomy for Bladder Cancer in Elderly Patients with Ileal Orthotopic Neobladder or Ileal Conduit: Results from a Multicentre Cross-Sectional Study Using Validated Questionnaires

Abstract: Objective: To evaluate health-related quality of life (HR-QoL) outcomes in elderly patients with different type of urinary diversion (UD), ileal conduit (IC) and ileal orthotopic neobladder (IONB), after radical cystectomy (RC) for bladder cancer, by using validated self-reported cancer-specific instruments. Patients and Methods: We retrospectively reviewed 77 patients who received an IC or an IONB after RC. HR-QoL was assessed with specific and validated disease questionnaires, administered at last follow-up.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…We found that choosing to perform a continent diversion was more frequent in younger patients, males, and those without comorbidities, treated in high-volume hospitals. This finding mirrors both the indication of a continent diversion together with a better quality of life achievable in this part of the population [15][16][17].…”
Section: Discussionsupporting
confidence: 75%
“…We found that choosing to perform a continent diversion was more frequent in younger patients, males, and those without comorbidities, treated in high-volume hospitals. This finding mirrors both the indication of a continent diversion together with a better quality of life achievable in this part of the population [15][16][17].…”
Section: Discussionsupporting
confidence: 75%
“…In addition, at a 3-year follow-up, the HR-QoL was even worse compared to 1-year follow-up, probably, because of the loss of hope for a successful recovery. Thus, ensuring more than 36 months of follow-up was found to be a critical factor in terms of postoperative changes in HR-QoL [ 24 ]. Follow-up duration of our study was consistent with the recommendations above.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, ONB is often performed on the younger and fitter patients, although Cerruto et al [9] observed in 2018 that ONB might be a good option in the elderly patient as well. Comparing ONB and ileal conduit after radical cystectomy in patients over 75 years of age, no significant difference was found regarding HRQOL.…”
Section: Orthotopic Neobladder and Ileal Conduitmentioning
confidence: 99%